Development of a Scale of Professional Competence of Preschool Teachers - Nguyen, Hien Thi; Nguyen, Thu Sy (Vietnam Journal of Education, 2023)
Circular 26/2018/TT-BGDĐT of Vietnam’s Ministry of Education and Training promulgates standards, policies and guidelines for measuring and assessing professional competences of preschool teachers in Vietnam. However, this set of standards has not yet met the requirements of action research on professional competences of preschool teachers. Therefore, this study aims to construct a valid and reliable self-reporting scale to measure the competences of preschool teachers in performing their work in preschools as one of the tools for impact assessment. The researchers approached Johnson’s theory of action research (2008) to research and develop a competency assessment toolkit according to 4 components of professional competences of preschool teachers (knowledge and understanding, operational skills, self development skills, social interaction skills). The validity and reliability of the scale was established by examining the responses of 186 preschool teachers of the selected preschool educational institutions in Southeast provinces in Vietnam. Cronbach’s alpha was also calculated as an internal consistency measure for the scale. Therefore, the findings of this study provide important evidence of the validity and reliability of the preschool teacher professional competency assessment standards.